Kebijakan Impor Indonesia Atas Produk Hewan Pasca Putusan Mahkamah Konstitusi Nomor 129/PUU-XIII/2015 - Irna Nurhayati; Aminoto Aminoto (Jurnal Konstitusi, 2022)
This article examines on how Indonesia’s import policy on animal products after the decision of Constitutional Court Number 129/PUU-XIII/2015 should be improved in accordance with the legislation formation and international trade rule. This article was based on normative juridical research supported by interviews with several officials of the Indonesian Ministry of Trade in Jakarta, and focus group discussion with some academics of the Universitas Gadjah Mada in Yogyakarta. The data were analyzed qualitatively using inductive approach. This article concludes that this Indonesia’s import policy is consistent with the formal principle of regulation formation, but does not fully comply with the substantive principle. This Indonesia’s import policy is in accordance with the regionalization and harmonization principles of the WTO SPS Agreement. However, it seems to be inconsistent with Article XI.1 GATT, because it requires certain conditions categorized as quantitative restrictions.